Optimization Of Injection Molding Parameters Fo Production Of Polypropylene Plastic Tray Using Taguchi Method - Wan, Kok Seong (Universiti Sains Malaysia, 2005)
In this study, the Taguchi method as a powerful design of experiments (DOE) tool developed by G. Taguchi is used to find the optimal process parameters for Battenfeld TM750/210 injection molding machine that was used to produce polypropylene (PP) plastic tray. Therefore, an orthogonal array (OA), main effect, the signal-to-noise (S/N) ratio, and analysis of variance (ANOVA) are employed to investigate the process parameters in order to achieve optimum bending deflection performance and optimum shrinkage behavior of a PP plastic tray so as to get maximum bending strength and minimum shrinkage respectively. Through this study, not only can the optimal process parameters for injection molding process be obtained, but also the main process parameters that affect the bending performance and shrinkage behavior of the PP plastic tray can be found respectively. Experimental results are provided to confirm the effectiveness of this approach.